Managerial competencies and competitive advantage in pharmaceutical blockbusters - Olafenwa, Abiodun Taiwo; Ojikutu, Ahmed Adeniyi; Owoeye, Oladapo Alani (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2021)
The study empirically tested the relationship between managerial competencies and competitive advantage in pharmaceutical blockbusters. According to the literature, blockbuster models and competitive strategies are significant determinants in organisational performance in the pharmaceutical industry context. However, the focus of this study is to determine whether efforts to combine managerial competence and the blockbuster model will reorient pharmaceutical companies to better competitive advantage by creating blockbuster drugs for the companies. This competitive advantage will position pharmaceutical companies in the face of increasing labour turnover, daunting economic challenges and perceived customer benefits that characterise this industry. A quantitative research design was adopted for this study, and primary data were obtained through a structured questionnaire administered to 22 managers of two major pharmaceutical firms in Lagos, Nigeria. The data obtained revealed a strong positive relationship between managerial competencies, blockbuster models and competitive advantage and three out of four hypotheses were accepted. The hypotheses were tested through Pearson’s product-moment correlation and regression product of determination. Descriptive statistical tools, ANOVA and multiple linear regressions were used to assess perceptions of managerial competencies and blockbuster models on SPSS (version 23.0). Cronbach’s alpha was extracted as a reliability coefficient for the data analysis (α = 0.851). Several implications for management and policy are also discussed in light of the findings of this study. It was concluded that a deep knowledge of managerial competencies and blockbuster models are highly needed in the selected pharmaceutical companies to gain business expansion, maintain low average costs and achieve significant market share while improving on their level of service delivery and capacity to support groups or teams through training, coaching and sharing specialist knowledge. This study recommends developing strategies and deploying blockbuster models across all industries for a distinctive advantage of ineffective organisational performance and greater productivity.